Effects of neutron–gamma radiation on the free radical contents in epoxy resin: upconversion luminescence and structural stabilization - Kacem, I.; Daoudi, M.; Dridi, W.; Sellemi, H.; Harzli, K.; De Izzara, G.; Geslot, B.; Guermazi, H.; Blaise, P.; Hosni, F.; Al-Hossainy, Ahmed F.; Bourezgui, A.; et al. (Applied physics. A, Materials science & processing, 2019)
The purpose of this work is to study the effect of mixed neutron–gamma radiation (MNGR) on structural, optical and paramagnetic properties on epoxy resin nanostructure thin films [ER] NSTF . These films were prepared and irradiated in the nuclear reactor with dose range between 100 and 900 Gy. After exposure to MNGR, FT-IR results demonstrated the broad ν (OH) and ν (C=O) band to increase with increase in radiation dose, while the ν (C–H) band decreased with increase in radiation dose. This is due to the formation of chain stretch, bending and scission/cross-linking through MNGR that lead to a decrease in the crystallinity region contained within the [ER] NSTF . XRD data confirm these results and show that the crystalline phase was destroyed by MNGR irradiation. PL is used to determine the fundamental transition and defects transitions in [ER] NSTF at 300 K. It was found that MNGR leads to significant enhancement of the luminescence properties. Samples of [ER] NSTF irradiated with 600 Gy dose presented the highest response. Therefore, EPR results confirmed that MNGR induces the paramagnetic center’s formation of the [ER] NSTF whose concentration varies differently.